Large bowel obstruction during pregnancy: the efficacy of dietary fibers - Yu.E. Dobrokhotova; E.I. Borovkova; T.D. Simonyan; D.S. Selimshaeva (LCC «Medicine-Inform», 2021)
Yu.E. Dobrokhotova, E.I. Borovkova, T.D. Simonyan, D.S. Selimshaeva Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to evaluate the clinical efficacy of dietary fibers and lactulose in pregnant women with large bowel obstruction. Patients and Methods: this prospective study included 60 pregnant women (20-24 weeks of pregnancy) with large bowel obstruction occurred during pregnancy and persisted for at least 3 months. All women were randomized and divided into two groups. Group 1 received soluble fibers and group 2 received group 2 received lactulose. Clinical efficacy of treatment was evaluated using a specialized questionnaire filled at baseline, 48 h, 4 days, and 14 days after starting treatment. Results: mean age was 27.1±4.0 years in group 1 and 28.3±5.0 years in group 2. Bowel evacuation less than 3 times a week occurred in 87% and 77%, respectively, the duration of pushing occupied more than 25% of defecation in 70% and 60%, respectively, hard stool occurred in 100%, anal fissures and a feeling of incomplete evacuation were reported in 47% and 57%, respectively. Comfort bowel evacuation 48 h after starting treatment was reported in 63% of women who received dietary fibers and 47% of patients who received lactulose. Normal defecation by day 4 was observed in 80% of women in group 1 and 53% in group 2. Treatment effect was achieved by day 14 in 87% in group 1 and 70% in group 2. The most common complaint was abdominal distension that occurred 3.5 times more common after treatment with lactulose (р<0.05). Conclusions: dietary fibers were more effective in terms of achieving the desired outcome and patient satisfaction. Keywords: large bowel obstruction, defecation, pregnancy, dietary fibers, OptiFibere, lactulose. For citation: Dobrokhotova Yu.E., Borovkova E.I., Simonyan T.D., Selimshaeva D.S. Large bowel obstruction during pregnancy: the efficacy of dietary fibers. Russian Journal of Woman and Child Health. 2021;4(1):36-41. DOI: 10.32364/2618-8430-2021-4-1-36-41.